2021
DOI: 10.3390/ijms22083970
|View full text |Cite
|
Sign up to set email alerts
|

Diversified Stimuli-Induced Inflammatory Pathways Cause Skin Pigmentation

Abstract: The production of melanin pigments by melanocytes and their quantity, quality, and distribution play a decisive role in determining human skin, eye, and hair color, and protect the skin from adverse effects of ultraviolet radiation (UVR) and oxidative stress from various environmental pollutants. Melanocytes reside in the basal layer of the interfollicular epidermis and are compensated by melanocyte stem cells in the follicular bulge area. Various stimuli such as eczema, microbial infection, ultraviolet light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 167 publications
(219 reference statements)
0
33
0
Order By: Relevance
“…(Gilchrest et al, 1981) These keratinocyte‐derived factors bind to their specific receptors, located on the melanocyte cell membrane, and activate various signaling pathways, such as the cyclic AMP/protein kinase A pathway, which are involved in the proliferation and differentiation of melanoblasts into melanocytes. (Hossain et al, 2021) Keratinocytes also modulate melanogenesis following ultraviolet (UV) irradiation. (Cichorek et al, 2013) It has been shown that keratinocytes release various inflammatory cytokines including interleukins (IL)‐18, IL‐33, and granulocyte‐monocyte colony stimulating factor (GM‐CSF).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(Gilchrest et al, 1981) These keratinocyte‐derived factors bind to their specific receptors, located on the melanocyte cell membrane, and activate various signaling pathways, such as the cyclic AMP/protein kinase A pathway, which are involved in the proliferation and differentiation of melanoblasts into melanocytes. (Hossain et al, 2021) Keratinocytes also modulate melanogenesis following ultraviolet (UV) irradiation. (Cichorek et al, 2013) It has been shown that keratinocytes release various inflammatory cytokines including interleukins (IL)‐18, IL‐33, and granulocyte‐monocyte colony stimulating factor (GM‐CSF).…”
Section: Discussionmentioning
confidence: 99%
“…(Cichorek et al, 2013) To prevent excess production of melanin, these same cytokines, via a negative feedback loop, regulate UV induced melanogenesis and inhibit melanogenesis by downregulating tyrosinase gene expression via activation of NF‐KB. (Hossain et al, 2021)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanocytes reside in the basal layer of the epidermis and they shield skin surface from UV radiation through melanin production, thus playing an important protective role [30]. Some authors tried to produce skin models including also this cell type, with different outcomes [31][32][33] (Table 1).…”
Section: Current Applications and Future Perspectivesmentioning
confidence: 99%